2018
DOI: 10.18512/1980-6477/rbms.v17n1p15-26
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrients Absorption and Dry Matter Accumulation in Grain Sorghum

Abstract: -The present study aimed to determine the curves of macronutrients and dry matter accumulation in grain sorghum DKB 599, grown in a semiarid region. A field experiment was conducted on a sandy loam eutrophic red Latosol (Oxisol) in Janaúba, State of Minas Gerais (MG), Brazil, in a randomized block design with four replications.As statistical method, a nonlinear regression, sigmoidal function with three parameters was used. After drying, the plants were weighed and ground to determine N, P, K, Ca, Mg and S conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
(7 reference statements)
1
5
0
Order By: Relevance
“…In the Brazilian Cerrado region, the practice of cultivating sorghum after the main crop at the end of the rainy season is increasing among farmers, mainly due to its better adaptability to irregular rainfall regimes in comparison to other crops, such as maize (Sodré-Filho et al, 2014;Cordeiro et al, 2015). Compared to other crops, sorghum's advantages include drought tolerance and adaptability to low-fertility and acid soils, common characteristics of the Cerrado region (Borges et al, 2018). The hypothesis that the presence of grasses would not affect sorghum performance was confirmed in the present study, although a number of authors concluded the opposite (Silva et al, 2017;Nakao et al, 2019) and observed losses in grain yield or dry matter production.…”
Section: Sorghum and Soybean Grain Yieldsupporting
confidence: 66%
See 3 more Smart Citations
“…In the Brazilian Cerrado region, the practice of cultivating sorghum after the main crop at the end of the rainy season is increasing among farmers, mainly due to its better adaptability to irregular rainfall regimes in comparison to other crops, such as maize (Sodré-Filho et al, 2014;Cordeiro et al, 2015). Compared to other crops, sorghum's advantages include drought tolerance and adaptability to low-fertility and acid soils, common characteristics of the Cerrado region (Borges et al, 2018). The hypothesis that the presence of grasses would not affect sorghum performance was confirmed in the present study, although a number of authors concluded the opposite (Silva et al, 2017;Nakao et al, 2019) and observed losses in grain yield or dry matter production.…”
Section: Sorghum and Soybean Grain Yieldsupporting
confidence: 66%
“…Reduced row spacing also increases the distance between plants in the row, and may reduce the competition between plants over water, light and nutrients (Borges et al, 2018;Francisquini-Junior et al, 2020). There were no differences between systems intercropped with sorghum, neither in the interactions of the species, nor in row spacing (p > 0.05), in terms of sorghum plants' height, weight of 1,000 grains and yield (Table 2).…”
Section: Sorghum and Soybean Grain Yieldmentioning
confidence: 98%
See 2 more Smart Citations
“…Sorghum (Sorghum bicolor L. Moench) shows good perspectives for plant residue production prior to soybean (Glycine max L.) as the summer crop because of its higher accumulated biomass and tolerance to water stress (Borges et al, 2018). It can also be intercropped as an alternative to grazing during low pasture availability (Santos et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%